Iconographical Approach in the Art of Hinduism: A Study of Pranāmī Temple at Malkā Hāns - Saima Sharif; Prof. Dr. Shaukat Mahmood (Al-Qamar, 2020)
This study comprises on the identification and documentation of inter cultural influences within the aesthetical manifestation of wall painting (frescoes). Mostly frescos has vanished their painterly qualities but still their remaining give a glimpses of aesthetic appeal. Without understanding the visual conception of frescoes at Parnāmī Temple, it is difficult to understand its philosophical approach of reality. The significance of frescoes in Hinduism can be appraised by religious mythology. Such indistinguishable phenomenon has been ensued in the religious architectural structure of Pranāmī Temple at Malkā Hāns during the period of subcontinent. Visual syntax plays an integral part in the architecture of Pranāmī Temple. The dynamic characterization of frescos is the evidence that this temple is prominent among its devotees and shows their psychological approach towards religious emotions of artists.